Hydrogenolysis of HCFC-142b over supported palladium catalyst - Lee, KH; Seo, KW; Mok, YI; Park, KY; Ahn, BS (KOREAN SOC INDUSTRIAL ENGINEERING CHEMISTRY, 2000)
1 1-Difluoroethane (HFC-152a), 1,1,1-trifluoroethane (HFC-143a), and ethane were mainly produced through the hydrogenolysis of 1-chlro-1,1-difluoroethane (HCFC-142b) over palladium on activated carbon (Pd/C) catalysts. Several types of activated carbon and various methods for the pretreatment of the support were used for impregnating the palladium. Depending on the method of pretreating the activated carbon with base and/or acid, the catalyst activity showed the following trend; 0.5 M NaOH and 0.5 M HCl>0.5 M HCl>0.5 M HNO3>0.5 M HF>non-pretreated carbon. The granular-type catalyst exhibited the highest conversion and selectivity to HFC-152a.
Keywords: SELECTIVE HYDROGENOLYSIS; CCL2F2 CFC-12; CH2F2 HFC-32; ACTIVATED CARBON